Гамазовые клещи гнезд береговой ласточки в Центральной Лесостепи УССР - Щербак, Г.И.; Балан, П.Г. (Вестник зоологии, 1982)
63 Gamasid mite species of 13 families were found in 192 nests of Riparia riparia L. during a year-over observation in Trakhtemirov village, Cherkassy Region,Ukrainian SSR. Seasonal changes in the specific variety and abundance are shown, a dominating species group is outlined.